Wikis and forums for collaborative problem-based activity: A systematic comparison of learners' interactions - Ioannou, Andri; Brown, Scott W.; Artino, Anthony R. (My University, 2015)
This article describes an experimental study that evaluated differences in students' discourse and actions when they used a wiki with discussion (i.e., an enhanced wiki) vs. a forum with attached MS Word documents for asynchronous collaboration on two case problems. The study used a counterbalanced within-subject design with 34 online learners working in small groups. A systematic content analysis of learners' interactions coupled with visual, analytical techniques showed within-group differences in using the technologies. The study revealed the expanding nature of a forum and the condensing nature of a wiki. Also, findings suggest that in a wiki, groups tend to be more collaborative, whereas in a threaded discussion, groups tend to be more cooperative. The study provides insights for instructors who use wikis and forums in their online courses to support collaborative problem-based activity.
Keywords: Collaborative learning; Forum; MediaWiki; Online discussion; Problem-based learning; Threaded discussion; Wiki